2010
DOI: 10.1371/journal.pone.0012291
|View full text |Cite
|
Sign up to set email alerts
|

Lying about the Valence of Affective Pictures: An fMRI Study

Abstract: The neural correlates of lying about affective information were studied using a functional magnetic resonance imaging (fMRI) methodology. Specifically, 13 healthy right-handed Chinese men were instructed to lie about the valence, positive or negative, of pictures selected from the International Affective Picture System (IAPS) while their brain activity was scanned by a 3T Philip Achieva scanner. The key finding is that the neural activity associated with deception is valence-related. Comparing to telling the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 67 publications
4
45
0
Order By: Relevance
“…For instance, Lee et al (55) observed higher neural activation in precuneus during recollection of prior negative affective events. Levine et al (58) found episodic autobiographical remembering compared to personal semantic, general episodic memory, or semantic knowledge to elicit increased neural activation in posterior midline cortex including precuneus.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lee et al (55) observed higher neural activation in precuneus during recollection of prior negative affective events. Levine et al (58) found episodic autobiographical remembering compared to personal semantic, general episodic memory, or semantic knowledge to elicit increased neural activation in posterior midline cortex including precuneus.…”
Section: Discussionmentioning
confidence: 99%
“…SPIONs were developed specifically as an MR imaging contrast agent, yet advances in coating technologies have allowed for the addition of other functional imaging moieties including those for optical 32,85,86 (e.g. fluorophores) and nuclear imaging 83,87,88 (e.g.…”
Section: Important Spion Design Parametersmentioning
confidence: 99%
“…Neuroscience research supports the link between EF and deception by providing evidence for underlying brain regions that are associated with both capacities. Deception recruits regions of the prefrontal cortex and medial frontal cortex, such as the anterior cingulate cortex (Abe, Suzuki, Mori, Itoh, & Fujii, 2007; Langleben et al, 2002; Lee, Lee, Raine, & Chan, 2010; Luan Phan et al, 2005), thought to be key regions underlying EF (Bunge, Ochsner, Desmond, Glover, & Gabrieli, 2001; Carter et al, 2000; Miller, 2000). Furthermore, modulation of the dorsolateral prefrontal cortex, a brain region associated with working memory (Fregni et al, 2005; Smith & Jonides, 1997) via transcranial direct current stimulation, changed the speed and efficiency of deception in adults (Priori et al, 2008).…”
Section: Executive Function and Temperamental Fear Concurrently Predimentioning
confidence: 99%